Motivations and barriers to cervical cancer screening among HIV infected women in HIV care: a qualitative study - Bukirwa, Agnes; Mutyoba, Joan N.; Mukasa, Barbara N.; Karamagi, Yvonne; Odiit, Mary; Kawuma, Esther; Wanyenze, Rhoda K. (BMC women's health, 2015)
Cervical cancer is the second commonest cancer in women worldwide and the commonest cancer among women in Uganda. Annual cervical screening is recommended for women living with HIV for early detection of abnormal cervical changes, however uptake remains grossly limited. This study assessed factors associated with cervical screening uptake among HIV infected women at Mildmay Uganda where cervical screening using Visual inspection with acetic acid and iodine (VIA and VILI) was integrated into HIV care since July 2009. Methods: Eighteen (18) in-depth interviews with HIV infected women and 6 key informant interviews with health care providers were conducted in April 2013 to assess client, health care provider and facility-related factors that affect cervical screening uptake. In-depth interview respondents included six HIV infected women in each of the following categories; women who had never screened, those who had screened once and missed follow-up annual screening, and those who had fully adhered to the annual screening schedule. Data was analyzed using content analysis method. Results: Motivations for cervical cancer screening included the need for comprehensive assessment, diagnosis, and management of all ailments to ensure good health, fear of consequences of cervical cancer, suspicion of being at risk and the desire to maintain a good relationship with health care workers. The following factors negatively impacted on uptake of cervical screening: Myths and misconceptions such as the belief that a woman’s ovaries and uterus could be removed during screening, fear of pain associated with cervical screening, fear of undressing and the need for women to preserve their privacy, low perceived cervical cancer risk, shortage of health workers to routinely provide cervical cancer education and screening, and competing priorities for both provider and patient time. Major barriers to repeat screening included limited knowledge and appreciation of the need for repeat screening, and lack of reminders. Conclusions: These findings highlight the need for client-centered counseling and support to overcome fears and misconceptions, and to innovatively address the human resource barriers to uptake of cervical cancer screening among HIV infected women.
Keywords: Cervical screening; Uptake; HIV positive women; Integrated HIV/ SRH services; Barriers; Motivators